Agreement Between HEDIS Performance Assessments in the VA and Medicare Advantage - Amal N. Trivedi MD, MPH; Ira B. Wilson MD, MSc; Mary E. Charlton PhD; Kenneth W. Kizer MD, MPH (SAGE Publishing, 2016)
Medicare Advantage (MA) plans and the Veterans Affairs (VA) health care system assess quality of care using standardized Healthcare Effectiveness Data and Information Set (HEDIS) performance measures. Little is known, however, about the relative accuracy of quality indicators for persons receiving care in more than one health care system. Among Veterans dually enrolled in an MA plan, we examined the agreement between MA and VA HEDIS assessments. Our study tested the hypothesis that private health plans underreport quality of care relative to a fully integrated delivery system utilizing a comprehensive electronic health record. Despite assessing the same individuals using identical measure specifications, reported VA performance was significantly better than reported MA performance for all 12 HEDIS measures. The VA's performance advantage ranged from 9.8% (glycosylated hemoglobin [HbA1c] < 7.0% in diabetes) to 54.7% (blood pressure < 140/90 mm Hg in diabetes). The overall agreement between VA and MA HEDIS assessments ranged from 38.5% to 62.6%. Performance rates derived from VA and MA aggregate data were 1.6% to 14.3% higher than those reported by VA alone. This analysis suggests that neither MA plans nor the VA fully capture quality of care information for dually enrolled persons. However, the VA's system-wide electronic health record may allow for more complete capture of quality information across multiple providers and settings.